Multielemental fingerprinting and geographic traceability of Theobroma cacao beans and cocoa products. (July 2016) - Bertoldi, Daniela; Barbero, Alice; Camin, Federica; Caligiani, Augusta; Larcher, Roberto
Abstract: Cocoa is a high-value commodity that appeals to the consumer's taste, but it is also renowned for its antioxidant and healthy properties. Many of these characteristics as well as flavour and its economic value depend on the geographic origin. This work reports the content of 56 macro-, micro- and trace-elements of 61 cocoa beans produced in 23 countries of East and West Africa, Asia and Central and South America using ICP-MS and tests the efficacy and robustness of a new chemometric approach of geographic traceability developed on the base of elemental profiles. The model based on the 29 elements (Ag, As, Ba, Be, Bi, Ca, Cd, Co, Cr, Cs, Cu, Fe, Ga, Hg, K, Li, Mg, Mn, Na, Ni, P, Rb, Se, Sr, Th, Tl, U, Y and Zn) indicated as the more predictive by the Discriminant Analysis provided an optimal discrimination among the 5 subcontinental origins, achieving 100% of correct re-classification. The model was cross-validated with satisfactory results (>85% correct reclassification). Finally, interesting opportunities were pointed out by the satisfactory application of this model in tracing back the subcontinental origin of 13 commercial samples of dark chocolate (77% correct reclassification). Highlights: The composition of 56 macro-, micro and trace elements in cocoa beans is reported. A new statistical model to identify cocoa origin using elemental profiles is developed. The model is cross-validated with satisfactory results. The model could be applied also for commercial dark chocolates.